2013
DOI: 10.1111/acem.12214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Council of Emergency Medicine Residency Directors' Standardized Letter of Recommendation in 2011-2012

Abstract: Objectives: The Council of Emergency Medicine Residency Directors (CORD) introduced the standardized letter of recommendation (SLOR) in 1997, and it has become a critical tool for assessing candidates for emergency medicine (EM) training. It has not itself been evaluated since the initial studies associated with its introduction. This study characterizes current SLOR use to evaluate whether it serves its intended purpose of being standardized, concise, and discriminating.Methods: This retrospective, multi-inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 15 publications
4
57
0
Order By: Relevance
“…However, letter writers rely disproportionately on the top two categories rather than the full scale for assessment. Our findings are consistent with another recently published description of SLOR distribution of responses 7. There may be a number of explanations for this, including that students may only choose writers with whom they have an outstanding rapport, in effect maximizing the likelihood of an outstanding evaluation.…”
Section: Discussionsupporting
confidence: 92%
“…However, letter writers rely disproportionately on the top two categories rather than the full scale for assessment. Our findings are consistent with another recently published description of SLOR distribution of responses 7. There may be a number of explanations for this, including that students may only choose writers with whom they have an outstanding rapport, in effect maximizing the likelihood of an outstanding evaluation.…”
Section: Discussionsupporting
confidence: 92%
“…1 Renamed the standardized letter of evaluation (SLOE) in 2013 2 , the intention of the SLOR/ SLOE was to make a standardized evaluation that could stratify students into quantiles based on performance during an emergency medicine (EM) rotation. 3 The SLOE replaces traditional narrative letters of recommendation for applicants to EM residency programs. Program directors (PDs) regard the SLOE as the most important item used for selecting applicants to interview.…”
mentioning
confidence: 99%
“…[12] The conflicting results from these studies are likely due to a number of factors, including substantial variability in content of LoR, [13] different criteria used in grading LoR, [1] and difficulty in reaching a consensus on what constitutes a good LoR, [14] The shortcomings of the LoR have led some specialties including emergency medicine to create a standard letter of evaluation that might allow for meaningful comparisons to peers and a global perspective on an applicant’s candidacy. [15, 16] One study, however, reported that the global assessment score component of the standardized letter of recommendation correlated poorly with a candidate’s rank order position in the residency match. [17] Because of reported difficulty of grading the content of the LoR, we chose to simplify analysis of the LoR by only analyzing the presence of laudatory comparative statements, rather than a wide variety of exemplary statements and other qualitative factors.…”
Section: Discussionmentioning
confidence: 99%